Guide to evaluate the simulation integration into the Medicine degree study plan: its evaluation in Cienfuegos - Mabel Rocha Vázquez; Dunia María Chávez Amaro; Víctor René Machado Navarro; Norma Mur Villar (Medisur)
Foundation: the use of simulation in university courses is a necessity that brings the student closer to the professional practice scenario and responds to patient safety. Objective: design a guide to evaluate the integration of simulation as a teaching-learning strategy in the Medicine career. Methods: development research based on dialectical materialism carried out at the Cienfuegos Medical Sciences University in 2023. Theoretical, empirical and mathematical statistical methods were applied that allowed the objective to be achieved. The proposed evaluation guide was organized into diagnosis and design stages. Results: the conception of simulation as a method from the study plan, the projection of the university to increase its use and the possibilities of methodological work to prepare teachers on the subject were identified as potentialities. The main limitations are the insufficient training of the faculty and the infrastructure lack. The proposal is derived from group work where integration criteria and strategic objectives were determined, and a guide was designed to evaluate the integration of simulation in the career study plan. The validation confirmed its relevance, feasibility, applicability and novelty as well as the agreement between experts. Conclusions: the guide makes it possible to evaluate the integration of simulation as a teaching-learning strategy in the Medicine degree. Its basis in the principles for the development of self-assessment and structuring by variables and indicators gives it novelty and responds to quality management.